Efficient Market Hypothesis: A Systematic Literature Review - Butet, Rossdelfhin; Kesuma, Sambas Ade (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The Efficient Market Hypothesis is a very important idea in today's money world, helping us understand how money markets work everywhere. This organized study of existing writings carefully looks at the ideas and proof connected to the Efficient Market Hypothesis. The study looks closely at its three types: weak, semi-strong, and strong, along with ideas like investors acting wisely and prices changing randomly. The findings reveal uncertain proof about whether this idea works all the time. Some studies agree, suggesting that market prices quickly show all available information. However, the existence of unusual market behaviors constantly challenges this idea. These differences are often described by emotional factors learned in the study of behavioral finance, which go against the idea that market players always make reasonable choices. Special focus is given to market situations that often show clear weak-form problems. This mainly happens because of uneven information levels and greater market changes. The study of existing writings finally decides that while the Efficient Market Hypothesis is still the main way to look at markets, its ability to explain things needs extra help. It's important to add behavioral ideas to explain market differences we see, giving useful advice for creating strong investment plans, especially in growing economies.